2022
DOI: 10.12968/vetn.2022.13.10.444
|View full text |Cite
|
Sign up to set email alerts
|

The sustainable pet food dilemma

Abstract: Every aspect of pet ownership has some environmental footprint, whether it is the food they eat, the toys they play with or the faeces they produce. Some of these environmental factors can be influenced by pet owners and healthcare providers, while others cannot. Studies considering the most eco-friendly pets ranked tortoises, rats and mice among the lowest impact pets to keep, with large breed dogs and horses the least eco friendly. These ratings were based on a variety of factors, including the pet's dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As shown in this study, the effects of meat-based dog and cat food, are marked. Others (e.g., [ 7 , 100 ]) have suggested that animals with lower dietary requirements (e.g., cats, small dogs), or herbivorous animals (e.g., horses, rabbits and rodents), could be kept instead. This has some merit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in this study, the effects of meat-based dog and cat food, are marked. Others (e.g., [ 7 , 100 ]) have suggested that animals with lower dietary requirements (e.g., cats, small dogs), or herbivorous animals (e.g., horses, rabbits and rodents), could be kept instead. This has some merit.…”
Section: Discussionmentioning
confidence: 99%
“…These compare favourably to those found within other dog foods [ 104 ]. Many other nutritionally-sound vegan dog and cat foods already exist [ 100 ], and this sector is growing rapidly [ 51 ]. It is likely that the most effective way to reduce environmental impacts associated with guardianship of companion animals, is to transition them on to nutritionally-sound vegan diets.…”
Section: Discussionmentioning
confidence: 99%